2019
DOI: 10.1186/s12874-019-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of attrition bias in Cochrane systematic reviews are highly inconsistent and thus hindering trial comparability

Abstract: Background An important part of the systematic review methodology is appraisal of the risk of bias in included studies. Cochrane systematic reviews are considered golden standard regarding systematic review methodology, but Cochrane’s instructions for assessing risk of attrition bias are vague, which may lead to inconsistencies in authors’ assessments. The aim of this study was to analyze consistency of judgments and support for judgments of attrition bias in Cochrane reviews of interventions publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…To reduce bias, we made independent assessments by two authors for each analyzed domain and sub-domain. Additionally, we included in the analysis only the first four domains of the Cochrane RoB tool, because instructions from the Cochrane Handbook for these four domains are better characterized compared to the remaining three domains [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce bias, we made independent assessments by two authors for each analyzed domain and sub-domain. Additionally, we included in the analysis only the first four domains of the Cochrane RoB tool, because instructions from the Cochrane Handbook for these four domains are better characterized compared to the remaining three domains [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, RoB assessments made by authors of published systematic reviews should not be taken at the face value, as we have shown in multiple studies that RoB assessments in many Cochrane reviews were inadequate and inconsistent [7][8][9][10][11][12][13][14]. Due to the specificities of surgical trials, we hypothesized that assessments of surgical trials may be more accurate and more consistent, compared to RCTs of nonsurgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study is that we considered only dichotomous outcome data; methods for handling missing continuous data are different and our findings might not be generalisable to systematic reviews of continuous outcomes 2930. Our sample consisted of systematic reviews that were published in 2012 and these might not reflect more current reviews; however, recent surveys have found that the reporting, handling, and assessment of risk of bias in relation to missing data has not improved over the date of our search 7313233. For further confirmation that current practice is unlikely to have changed, we assessed the reporting and handling of missing data in a sample of recently published systematic reviews.…”
Section: Discussionmentioning
confidence: 97%
“… 29 30 Our sample consisted of systematic reviews that were published in 2012 and these might not reflect more current reviews; however, recent surveys have found that the reporting, handling, and assessment of risk of bias in relation to missing data has not improved over the date of our search. 7 31 32 33 For further confirmation that current practice is unlikely to have changed, we assessed the reporting and handling of missing data in a sample of recently published systematic reviews. To make our selection of a sample of systematic reviews reproducible, we ordered systematic reviews published from January 2020 in the chronological order of their publication and selected the first 15 that met our eligibility criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane risk of bias (RoB) tool, with seven dimensions, including sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessors, incomplete outcome data, selective outcome reporting and other potential threats to study validity will be used. We will assess RoB in line with instructions from the Cochrane Handbook for Systematic Reviews of Interventions22 to avoid mistakes review authors frequently make when conducting RoB assessments with this tool 23–27. For each study, we will create a RoB domain, which will have a RoB judgement for each domain (high, low or unclear risk) and an accompanying supporting comment to explain the RoB judgement.…”
Section: Methods and Analysismentioning
confidence: 99%